Change in voting Singapore's 2015 General Election - Lee, Terence 1972-; Tan, Kevin (Ethos Books, 2016)
For Singaporeans, the year 2015 will be remembered for its grand celebrations of the nation's 50th year of independence (SG50), as well as the demise of founding Prime Minister Lee Kuan Yew. It was also the year the PAP government recaptured its electoral hyper dominance at Singapore's 13th General Election held on 11 September 2015. This volume analyses the unexpected results of yet another historic election and considers why a change in voting ensued after the 'watershed' polls in 2011. Sixteen well-regarded scholars and political observers uncover the key issues raised and evaluate the impact of the 2015 general election from the perspectives of law, history, politics, media, culture and sociology.